Pengaruh Layanan Rehabilitasi terhadap Kualitas Hidup Mantan Pecandu Narkotika dalam Menjalani Rehabilitasi di Klinik Pratama BNN Kota Sawahlunto - Mincia, Hasta Henwi; Yuliarti, Yuliarti (Lembaga Yasin AlSys, 2025)
The recurrence of drug use among clients after undergoing rehabilitation highlights the need to improve the quality of rehabilitation services to support long-term recovery. This study aims to analyze the effect of rehabilitation services on the quality of life of former drug addicts at the Pratama Clinic of the National Narcotics Board (BNN) in Sawahlunto City. A quantitative approach was used with a descriptive method and simple linear regression analysis. The population consisted of 35 rehabilitation clients from 2023–2024, all of whom were selected as the sample using a total sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability (Cronbach’s Alpha > 0.6). The analysis results show that rehabilitation services have a positive and significant effect on clients’ quality of life, with a correlation coefficient (R) of 0.485 and a coefficient of determination (R²) of 0.235, indicating that rehabilitation services contribute 23.5% to the improvement of former addicts' quality of life. The t-test yielded a value of t = 3.185 with a significance level of 0.003 < 0.05, thus supporting the hypothesis. These findings reinforce the SERVQUAL theory, which emphasizes the importance of empathy, reliability, and responsiveness in rehabilitation services to support sustainable recovery and social reintegration of clients.